THE EFFECT OF VARIATION IN THE CONCENTRATION OF GREEN TEA LEAF EXTRACT (Camellia sinensis (L.) Kuntze) ON THE PHYSICAL QUALITY OF EYE CREAM PREPARATIONS - sulistiawati, Nofita; Putriana Rahman, Alief; H, Syaifiyatul (Acta Pharmaceutica Indonesia, 2025)
Premature aging of the eye area is characterized by the appearance of wrinkles, fine lines, eye bags and dark circles due to exposure to ultraviolet (UV) light, free radicals, and decreased collagen production. Green tea leaves (Camellia sinensis (L.) Kuntze) are known to contain high antioxidants, especially catechins such as epigallocatechin gallate (EGCG), so it has the potential to be used as an anti-aging agent to slow down the skin aging process. This study aims to determine the effect of variations in green tea leaf extract concentration on the physical quality of eye cream preparations and determine the best formula. The study was conducted experimentally with four eye cream formulas, namely formula 0 (0% extract), formula 1 (0.5% extract), formula 2 (5% extract), and formula 3 (10% extract). Physical quality evaluation included organoleptic test, homogeneity, pH, viscosity, spreadability, stickiness, cream type, and centrifugation test. Data were analyzed using One-Way ANOVA test and compared with eye cream physical quality standards. The results showed significant differences (p < 0.05) in the parameters of pH, viscosity, spreadability, and stickiness between formulas. Formula 1 (0.5%) fulfilled all physical quality parameters according to the standard, including even homogeneity, pH according to the skin, optimal viscosity and spreadability, and no phase separation. It was concluded that formula 1 was the best formula.